Plant development and biotechnology - Trigiano, R. N. (Robert Nicholas) 1953-; Gray, Dennis J. (Dennis John) 1953- (CRC Press, 2005)
Biotechnology revolutionized traditional plant breeding programs. This rapid change produced new discussions on techniques and opportunities for commerce, as well as a fear of the unknown. Plant Development and Biotechnology addresses the major issues of the field, with chapters on broad topics written by specialists. The book applies an informal style that addresses the major aspects of development and biotechnology with minimal references, without sacrificing information or accuracy.---Publisher's description